Materials development training for ABET workers. - Alkenbrack, Betsy (My University, 2014)
The aim of this study was to develop a high-quality, experience-based, accredited training course that would bring black literacy workers into the ABET materials writing field. The report begins by setting the context of ABET in South Africa, then describing the literature on a wide variety of materials development projects in South Africa and other developing countries, some of which can be used as models for the proposed course. Training courses in fields outside ABET also inform the study. Through a combination of questionnaires and interviews, the study explores the needs of institutions concerned with ABET materials as well as the needs and skills of potential trainees. Ten specialists were interviewed: Seven were ABET practitioners representing a tertiary institution, NGOs and government and three were involved in educational publishing.They identified the need for relevant practical materials in all South African languages and learning areas, and said a training course should stress thinking skills, writing skills, visual literacy and a firm grasp of the process and economics of book production. Thirty eight potential trainees were contacted through questionnaires and focus groups. They were positive about the proposed course and alerted the researcher to logistical issues regarding finances and timing. All respondents said the course must be accredited in line with NQF requirements. The main tension that arose in the interviews was around priorities. While all the experts said training in the production of materials was important, it had to viewed as a luxury in light of extremely limited resources and urgent demands for delivery. Finally a proposed course is described, consisting of a 12-module, part-time course lasting approximately one year.
Keywords: Adult education teachers--Training of--South Africa; Adult education--South Africa; Basic education--South Africa; Literacy programs--South Africa